Technical Change, Markup, Divestiture, and Productivity Growth in the U.S. Telecommunications Industry - Nadiri, M. Ishaq; Nandi, Banani (The Review of Economics and Statistics, 1999)
This paper examines the sources of productivity growth for the, U.S. telecommunications industry from 1935 to 1987. These years encompass both the pre-and post-AT&T divestiture periods. We formulate a structural model that accounts for both changes in the cost and the demand side of the industry. We measure the contributions of aggregate demand, information intensity of the economy, price-cost margins, relative factor prices, direct and indirect effects of technological progress, and R&D investment on total-factor productivity (TFP) growth rate. We show that TFP growth rate as conventionally measured is a seriously biased measure of rate of technical change in this industry.